Penerapan Pembelajaran Mind Mapping dalam Metode Quantum Learning pada Mata Pelajaran TIKuntuk Meningkatkan Hasil Belajar Siswa Kelas VII J (Studi Kasus: SMP Negeri 3 Singaraja Tahun Ajaran 2012/2013) - Venty Indriatna; I Gede Sudirtha; Dessy Seri Wahyuni (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
This research’s aims is to know the improvement of student’s learning outcomes in the subjects of information and communication technologies (TIK) by applying techniques of mind mapping which is part of the learning quantum learning method, and determine students' response to the application of learning mind mapping.This study was conducted in SMP 3 Singaraja, which involves the students of class VII J (30 students) of the academic year 2012/2013.Based on learning outcomes of students in class VII J semester academic year 2012/2013 shows that classical completeness in this class is below the standards set by the school. The study design was a Classroom Action Research (CAR), which consists of 2 cycles. The data collected in this study is the result of learning and student response terrhadap learning mind mapping application on TIK subjects. Student learning outcomes data were collected through a test of cognitive and affective and psychomotor observation sheet, while the student response data were collected with a questionnaire sheet enclosed.Capturing data on the test of cognitive held at the end of each cycle, while for observation sheet affective and psychomotor each run every meeting. The results showed that (1) there is an increase in student learning outcomes. (2) the average students' response to the application of the learning techniquesconsidered positive in mind mapping. The study concluded that the method of learning mind mapping application in quantum learning method in TIK subjects can improve learning outcomes and received a positive response from students.